Comparison of Building Structure Planning with SNI 2847-2013 Method and SAP2000 V.19 Software Code ACI 318-14 - Ada Bina Avizan; Koespiadi Koespiadi (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Building construction planning in Indonesia uses SNI 2847: 2013 regulatory guidelines especially in building planning. So we need a combination of standardization used with technological developments that are realized in a computer program to simplify and speed up calculations. The results of the calculation of beam structures and concrete columns in the final project calculations using SNI 2847: 2013 regulations and analysis using SAP2000 code ACI318-14 software obtained the results: a) In plimelinary beam designs with sizes B1 30/40 cm and B2 40/55 cm are not able hold the load on the structure (over strange), then the beam dimensions are enlarged to B1 30/60 cm and B2 40 / 60cm. In the SAP2000 output analysis results after the beam dimensions are enlarged there are no over strange frames and meet the strength of the structure. b) From the beam analysis planning on bending reinforcement using SNI 03-2847-2013 concrete reinforcement regulations and using SAP2000 code ACI318-14 software analysis, the number of reinforcement obtained is more using SNI 03-2847-2013 concrete reinforcement regulations compared to using software analysis SAP2000 code ACI318-14 the amount of reinforcement used has a difference of 0.17%. c). From the planning of column analysis on bending reinforcement using SNI 03-2847-2013 concrete reinforcement regulations and using SAP2000 code ACI318-14 software analysis, the same amount of reinforcement is obtained between calculations using SNI 03-2847-2013 concrete reinforcement regulations and using SAP2000 code ACI318 software analysis -14.